Phytochemical Screening and Antibacterial Activity of the Vacuum Liquid Chromatography Fractions of Mentha pulegium Growing in Iraq - Abed, Salam Ahmed; Hamdan, Alaa Abd Alhasan; H. Jassim, Ibrahim (Journal of Science and Mathematics Letters, 2022)
Mentha pulegium, a species of Lamiaceae family, is flowering plant native to Europe, North Africa and the Middle East. Crushed M. pulegium leaves exhibit a very strong fragrance like spearmint. The objective of the study was to investigate the phytochemical constituents and antibacterial activity of M. pulegium stems and leaves vacuum liquid chromatography (VLC) fractions. The powdered leaves and stems were macerated with absolute methanol then filtered using Buchner system. The filtrate was evaporated, then submitted to VLC using different solvents, and their fractions were collected. Phytochemical screening tests were done to investigate the chemical composition of methanol extract. The antibacterial effect of both methanol crude and the five extracts was studied on gram positive (S. aureus and S. haemolyticus) and gram negative (P. aeruginosa and K. pneumoniae) bacteria using minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The results indicate the presence of flavonoids, saponins, tannins in plant aerial parts with the presence of alkaloids but in a lesser degree. The result of antibacterial assay showed that MICs of methanol fraction were approximately 900 µg/ml for gram positive bacteria (S. aureus and S. haemolyticus), 225 µg/mL for P. aeruginosa and 450 µg/mL for K. pneumonia. While the best MBCs of the five fractions along with MOHM extract gave, the bactericidal effect in concentrations 450 μg/mL for P. aeruginosa. Our study is the first report on phytochemical screening and antibacterial activity of VLC fractions of Mentha pulegium.